Respuesta :
Answer:The solution is in the attached file
Step-by-step explanation:
![Ver imagen zibahkeshiro](https://us-static.z-dn.net/files/d95/46e91d726763b5c071bc5d5d69a77942.jpg)
Step-by-step explanation:
If we take 4 - 10y = 22 - 6x and make y the subject. After some simplifying and rearrangement, we will realize that it is equal to y = ³/₅ x + ⁹/₅
If 4 - 10y = 22 - 6x (subtract 4 from bothsides)
the -10y = 22 - 4 - 6x (divide both sides/ each term by 10)
- y = ¹⁸/₁₀ - ⁶/₁₀ x (multiply each term by - 1 and move x to the front of the RHS)
y = ³/₅ x + ⁹/₅